APLIKASI RUMUS PENAKSIRAN BOBOT BADAN TERNAK BERDASARKAN UKURAN DIMENSI TUBUH PADA KELOMPOK PETERNAK SAPI POTONG DI DESA DAUH YEH CANI ABIANSEMAL BADUNG - Suranjaya I .Gd; Kd. Anom Wiyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
The activity of community service in order to improve the knowledge and skill of farmer in estimating the live weight of Bali cattle was conducted on Monday, 23 August 2009. This activity was ateended by 22 farmers from the members of local society “Walung Sari” located at Banjar Banjaran, Abiansemal village, Badung regency. The methods used in this activity were counseling and demonstration including the procedure to measure body dimension which are body length and heart width of cattle, estimate a body weight by using a formula besed on body dimension, and comparing the estimation result into a table conversion. Result of the activity indicated that the response of farmers at that time was very good. This matter was shown from a good enthusiasm of farmers in attending the activity and the number of questions emerges at the time of discussion. The questions were raised all about equipments and how to use them in measuring body dimension, how to increase the estimation accuracy and how the impact of estimation result when it is used in animal transaction. At the time of demonstration all farmers participated on the practice with a good enthusiasm too and they also tried to measure a body dimension of cattle. From the activities result, it can be concluded that a training as well as estimate of a live weight based on that formula or equation have been perceived by the farmers and promised to apply this knowledge in animal transaction.